REVISITING THE CASTS FROM THE TAGUS VALEY (PORTUGAL): A POSSIBLE MEGALITHIC ENCLOSURE DEPICTION IN ROCK ART - Coimbra, Fernando (Revista Cuadernos de Arte Prehistorico, 2021)
The author analyses some engravings from Rock 132 of Fratel (Tagus Valley), which could constitute the representation of a megalithic enclosure datable from the Neolithic/Calcolithic, as those that exist, not so far, in Alentejo. In fact, although that rock is currently submerged by the waters of the dam of Fratel, the existence of a latex cast done in the 70‟ allows studying the mentioned engravings, which reveal a great typological similarity regarding the plan of the enclosure from Monte do Olival 1, having the engravings from Rock 132 also the representation of the gates, as it happens at enclosures such as Perdigões, Xancra and Chez-Reine (France). Other cases of what seems to be the representation of prehistoric architectonic elements in rock art are also analyzed. The author makes also a comparison between the plans of ditched enclosures from Spain and the UK and some rock art images.